Empathy profile of the students and faculty UP College of Dentistry - Tumang, Heherson M. (2002)
Current literature regarding the emerging importance of emotional intelligence for professional success has gained much attention since the early 1990's. Empathy, which is an essential construct of intrapersonal and interpersonal intelligence, is the focus of this study. It seeks to determine and explore the empathy profile of the College of Dentistry, University of the Philippines Manila in an attempt to obtain awareness to the role of empathy in dental education and professional competence. This is a descriptive study conducted from October 2001 to March 2002 at the University of the Philippines College of Dentistry. A total of 127 students from the preclinical and clinical dentistry proper and 35 faculty members participated in the study. To determine the empathy profile, two instruments were used: a) the Interpersonal Reactivity Index (IRI) devised by Davis-a dispositional measure of empathy and b) a set of nonverbal sensitivity or decoding tests by Mayer, Caruso and Solovey?a performance test of accuracy in identifying emotions in faces, designs, music and stories. Data obtained were processed and analyzed using measures of central tendency and distribution. The study also sought to determine if there is a difference in the profile of the students and faculty according to age, gender and experience. The empathy profiles in turn were also linked to self-report items of personal characteristics, security of family relations and parental discipline techniques. Correlations analysis was also conducted to determine the Pearson?s Product Moment Coefficients of Correlations. One way ANOVA was performed to determine if the empathy profile vary with age, gender, level of experience and the self-report items of the respondents. The results show that the students and faculty of the University of the Philippines College of Dentistry are normally empathic as seen from their Fantasy Scale (FS) and Empathic Concern (EC) scores. While Perspective Taking (PT) and Personal Distress (PD) scores showed higher values, this means that compared to the normative values, the respondents of the present study are more empathic on these measures. It is evident from the results of the Interpersonal Reactivity Index that the respondents generally scored high on the affective factor EC, which indicates that relatively the respondents have a tendency to respond to distress in others with the reactive response of sympathy, concern and compassion. Similarly, the high PT and FS scores indicate the respondent's likelihood of engaging in attempts to entertain the point of view of other people (PT) and to a lesser degree attempt to imagine themselves in the circumstances of another (FS). The low PD scores, which assess affective outcomes, is indicative that in the face of another's misfortune the respondents will likely not feel as anxious or uncomfortable of the state of mind of the other. The results indicate that there was specific variability in the empathy profile of the subjects. Gender and psychosocial development patterns emerged in the profile. For the Perspective Taking component, studies on this found significant relationship in a direct manner to self-esteem and other-oriented sensitivity, and inverse relationship to measures of social dysfunction, fearfulness, and self-oriented sensitivity. The faculty scored higher in this regard compared to the students, this confirming literature that Perspective Taking is significantly related to age. For the Fantasy component, studies on literature found this to be significantly related in a direct manner to emotional reactivity and other-oriented tendencies. The students in this study scored higher than the faculty. In contrast, the Personal Distress component was found to be significantly related in a direct manner to social dysfunction, emotional vulnerability, fearfulness, and self-oriented sensitivity, and inversely related to self-esteem as well as age. This is evident in the lower scores of the faculty on this measure. As to gender, females distinctly scored higher than male counterparts on the affective components of empathy. As to level of experience, results indicate that the Fantasy Scale and Personal Distress IRI subtests present a diminishing trend as one goes up the levels of experience; no noticeable difference was observed in the other two scores. Age was also seen to be positively correlated to Perspective Taking while negatively correlated to Personal Distress. In Perspective Taking, the faculty scored higher than their student counterparts. The results point to experience as a variable to emotional reactions to events in the environment. Those with more information about emotions are not disposed to readily or intensely react with greater effect to the observed experiences of others. Variability in nonverbal sensitivity or the ability to identify emotions in a variety of arousal modes was also evident in the results. The respondents performed similarly in identifying emotions in faces which was most likely due to the abilities of the respondents for direct association or labeling or an ability to draw from some form of classical conditioning. These modes of arousal operate largely automatically and without conscious direction by the observer. However, contrary to the principle mentioned there was an observed decline in identifying emotions in music and designs by level of experience. The results of the nonverbal Sensitivity tests parallel those of the IRI. It substantiates gender patterns reported on literature that females are more emphatic than their male counterparts. It revealed that the students were better at identifying emotions in stories. It terms of the composite score (total nonverbal sensitivity score), the students were more accurate at decoding emotions in a variety of arousal modes than the faculty. This shows that age is negatively correlated with the nonverbal tests particularly music, design, and the total Nonverbal Sensitivity test value. The ability to identify emotions in stories taken on advanced cognitive processes. It involves role taking and elaborated cognitive networks. This is related to Hoffman's mode of language mediated association which is determined by the observer's past experiences. This was seen in the results where the faculty obtained higher value for this measure. The self report reveals that the respondents of the study believe themselves to be emotional in temperament, and of secure family relations. Majority of the respondents reported either power assertion or induction as their parental discipline styles. Consequently, it is apparent that, as projected from self-reports on temperament, security of family relations and parental discipline the respondent gender and psychosocial development may have links on their empathy profiles. Temperament, security of family relations and induction as a parenting style are positively related to empathy. Emotionality shows positive correlation to the Fantasy Scale, Empathic Concern and Personal Distress. Sociability, activity and security of family relations are shown to be negatively correlated to Personal Distress.
Major project (Master of Health Professions Education)--University of the Philippines Manila
Keywords: Empathy